Motility of undiluted epididymal spermatozoa of hamster - Sucharee Nawikawanich (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Spontaneous motility and the effects of some physicochemical factors were studied on the whole undiluted spermatozoa obtained by in vivo micropuncture from different regions along the hamster epididymis. Motility was determined and scored subjectively on a unit of 0-10 by examining a spherical droplet of the sample under paraffin oil at 33°C with a dissecting microscope (80x magnification). 'Samples from the proximal and mid caput were quiescent, but those from the distal caput showed weak to moderate motility. The corpus epididymal spermatozoa exhibited most vigorous motility (SCORE, 7.1+0.2). Distal to this region, substantial decreases in motility occurred. Thus, samples from the proximal and mid cauda showed moderate and weak motility while those from the distal cauda and the epididymal vas were completely quiescent. Only those spermatozoa which showed spontaneous motility were affected by changing the temperature of incubation. During incubation at 37.4°C, motility of spermatozoa from the distal caput, the corpus and the proxi-mal and mid cauda were further increased. On the other hand those from the corpus and the mid cauda were significantly inhibited by lower-ing the incubation temperature to 28°C. Incubation of the corpus epi-didymal spermatozoa under anaerobic condition produced a significant and reversible inhibition of sperm motility. Incubation under 10 and 20 cmH2O above atmospheric pressure had a slight inhibitory effect on motility of the corpus spermatozoa. Dilution (1:10) of the corpus spermatozoa with 0.9% NaCl solution did not increase the activity. However, this effect was transient since the motility rapidly decreased compared to the undiluted controls. Similar dilution with sperm-free fluid (plasma) from the same region of the same animal had no effect but addition of the plasma from different animals immediately depressed the corpus sperm motility. Complete immobilization of the corpus sperma7 tozoaoccurredafter dilution with plasma from the cauda epididymidis. Activity of the immotile distal cauda spermatozoa could be initiated by dilutions with 0.9% NaC1 solution or plasma from the corpus region. Similar dilution with the cauda plasma failed to initiate motility of the cauda spermatozoa. Measurements of spermatocrit values along the epididymal tubule revealed a profile which was opposite to that for sperm motility. The results suggest that the hamster epididymal spermatozoa are not virtually immotile in situ except those in the proximal and mid caput, the distal cauda, and the epididymal vas regions. The motility of the undiluted epididymal spermatozoa can be modulated by temperature, pressure and oxygen. Evidence from the dilution studies supports the previous findings that there presents an inhibitory factor, presumably a large molecular weight glycoprotein 'immobilin', in the cauda fluid. This factor helds cauda spermatozoa in a quiescent state by virtue of creating a high viscoelastic drag in the cauda plasma.